Linearly Scanning Spoof Surface Plasmon Polaritons Leaky-Wave Antenna With High Scanning Rate - Yue Wang; Shengying Liu; Chunsheng Guan; Hao Yu; Jinxiang Wang; Qun Wu; Changfei Zhou; Xumin Ding (IEEE Open Journal of Antennas and Propagation, 2024)
In this paper, a wide-angle linearly scanning leaky-wave antenna (LWA) based on spoof surface plasmon polaritons (SSPPs) with a very high scanning rate is proposed. A sine curve period is introduced to construct the SSPPs transmission line in the form of a sine curve, which can transform the dispersion curve to the fast wave region to realize the desired dispersion properties for linearly high scanning rate LWA. The simulated results show that the proposed LWA achieves a scanning angle range of 109° over a narrow operation bandwidth of 7.73–8.13 GHz, implying high linearity, and a high scanning rate. A prototype is fabricated and measured, indicating that the measured scanning angle range is 100° within the frequency band of 7.82–8.21 GHz, and the relative average scanning rate (RASR) is 2053.4°. Compared with ideal linear scanning in the operating frequency band, the mean absolute value error (MAVE) of the measured scanning angle-frequency curve is 1.032°, which validates the proposed design with good agreement between the simulated and measured results. The high scanning rate and scanning linearity performances of the LWAs exhibit great value in reducing both the occupation of electromagnetic spectrum resources and the requirements of accuracy for transmitters and receivers, respectively.